Science Technology, Ethics - Saputra, Muhamad Ajye; Imam Mukhlis (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Research Aims: Science and science technology are closely related to education, research and policy. Science technology is expected and obliged to apply ethics in all fields. The application of ethics in scientific technology starts from the educational sector, both academic and non-academic. Applying scientific ethics when conducting research can produce research results that are ethical or in accordance with the norms that apply in society. Scientific technology that applies scientific ethics will receive a positive perception by society. Scientific ethics in the field of scientific technology already exist informally and are strengthened by normative and formal policy rules. The scientific ethics policy was created not to limit the development of scientific technology, but to direct scientific technology in a direction that is in accordance with the norms that apply in society. This research method uses SLR (Literature Review system).